Unraveling The Moderating Role of Environmental, Social, and Governance in The Value Relevance of Earnings and Equity of Tax Avoidance - Dewangga Rexipal; Amrie Firmansyah (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study examines the value relevance of earnings and equity associated with tax avoidance and investigates the moderating role of environmental, social, and governance (ESG) performance. Using a purposive sampling method, this study analyzes 74 observations of companies listed in the LQ45 Index of the Indonesia Stock Exchange during the period 2022-2023. The analysis employs a price model based on Ohlson (1995) and multiple linear regression for panel data with robust standard errors. The results indicate that tax avoidance is positively associated with the value relevance of earnings but is not significantly related to equity. Furthermore, ESG performance weakens the positive relationship between tax avoidance and earnings value relevance, while it mitigates the negative relationship between tax avoidance and equity value relevance. These findings suggest that although tax avoidance enhances earnings-based valuation, strong ESG performance shifts investor focus toward long-term sustainability rather than short-term tax benefits. This study contributes to the literature on value relevance and tax avoidance by providing evidence on the moderating role of ESG in an emerging market context.